Differences in evolution of temperature, plastic deformation and wear in milling tools when up-milling and down-milling Ti6Al4V. (May 2022) - Kaltenbrunner, T.; Krückl, H.P.; Schnalzger, G.; Klünsner, T.; Teppernegg, T.; Czettl, C.; Ecker, W.
Abstract: Milling tools are subjected to severe loading conditions causing different wear mechanisms. Among others, the dominating tool wear mechanism depends on the combination of workpiece material and tool material, cutting parameters and the mode of operation. Usually, in industrial milling processes, the mode of operation is a combination of up- and down-milling. The present work is devoted to the question how up-milling and down-milling processes differ with respect to the thermomechanical loading and the tool wear, particularly in the case of milling titanium alloy Ti-6Al-4V. To this end, cutting tests for both modes of operation have been performed. The cutting inserts have been evaluated in certain intervals via optical and electron microscopy. Finite element simulations provide the corresponding thermal and mechanical loading at the cutting edge during service. Experiment and simulation consistently show the detrimental effect of up-milling in comparison to down-milling. However, the wear analysis suggests the same mechanism for both modes of operation but with higher rate of wear in up-milling. The cutting experiments show that wear is driven by the growth of fatigue cracks and thus indicate a mechanical reason for tool wear. From the simulations, it is clear that the specific interaction between thermal and mechanical loading in up-milling is the reason for accelerated tool wear in up-milling compared to down-milling. The higher rate of wear in up-milling is attributed to its specific thermomechanical loading. Highlights: 2D-modeling approach for circular shaped cutting inserts in Ti6Al4V milling Experimental and numerical investigation and correlation of local loading and wear Revealing the reason for accelerated wear in up-milling compared to down-milling Wear mechanism in Ti6Al4V milling is rather fatigue- than diffusion-controlled.